2017
DOI: 10.3390/rs9121220
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning Versus OBIA for Scattered Shrub Detection with Google Earth Imagery: Ziziphus lotus as Case Study

Abstract: There is a growing demand for accurate high-resolution land cover maps in many fields, e.g., in land-use planning and biodiversity conservation. Developing such maps has been traditionally performed using Object-Based Image Analysis (OBIA) methods, which usually reach good accuracies, but require a high human supervision and the best configuration for one image often cannot be extrapolated to a different image. Recently, deep learning Convolutional Neural Networks (CNNs) have shown outstanding results in objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
127
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 52 publications
(67 reference statements)
1
127
1
1
Order By: Relevance
“…Certainly, only the CNN can overcome the fact that the complexity of VHR images can cause traditional human-dependent classification models to fail due to the limited representation power of handcrafted features, 34 thereby obtaining class information from complex image blocks. It can be concluded that the proposed BOBIC method was successful at applying the CNN to OBIC, which also proves the hypothesis of Guirado et al 33 that stated that the inclusion of CNN-models could further improve OBIA methods.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Certainly, only the CNN can overcome the fact that the complexity of VHR images can cause traditional human-dependent classification models to fail due to the limited representation power of handcrafted features, 34 thereby obtaining class information from complex image blocks. It can be concluded that the proposed BOBIC method was successful at applying the CNN to OBIC, which also proves the hypothesis of Guirado et al 33 that stated that the inclusion of CNN-models could further improve OBIA methods.…”
Section: Discussionsupporting
confidence: 68%
“…Guirado et al 33 compared state-of-the-art OBIA methods with CNNbased methods for the detection of plant species of conservation concern and reasoned that adopting the CNN-based methods could further improve OBIA methods. Zhao et al 34 proposed a two-step OBIC framework using a combination of handcrafted and deep CNN features.…”
Section: Introductionmentioning
confidence: 99%
“…Future work must investigate the diversity of backgrounds and the size of image classes needed for model training. Similar tools are developing for screening camera trap images (Chen, Han, He, Kays, & Forrester, 2014), and finding organisms in remotely sensed imagery (Guirado, Tabik, Alcaraz-Segura, Cabello, & Herrera, 2017). Convolutional neural networks underlie many advances in these areas, and connecting insights across disciplines will be a key in developing best practices.…”
Section: Discussionmentioning
confidence: 99%
“…Google Earth images have only three bands: red, green, and blue (RGB). Owing to the poor spectral information, there have not been too many ISA or land-cover mapping studies based on Google Earth image, as they are mainly used for small object detection, such as village buildings [18], scattered shrubs [19], ships [20], and qanat shafts [21]. As a free high spatial resolution image data source, Google Earth has a high potential for high resolution ISA mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence techniques, such as deep learning, have shown a high performance of vegetation detection in high-resolution images [19]. Other geometric and textural features can also help reduce the confusion between ISA and soil.…”
mentioning
confidence: 99%